STRUKTUR DEMOGRAFI POPULASI Rhizophora apiculata DI KAWASAN INDUSTRI PERMINYAKAN PROVINSI RIAU - Syahrial Syahrial; Dietriech G Bengen; Tri Prartono; Bintal Amin (Universitas Teuku Umar, 2018)
The decline in mangrove vegetation density and the area of mangrove forests in the coastal province of Riau occurred due to the logging of mangrove forests and the conversion of mangrove forests into other uses such as industrial estates. This study aims to collect a database of mangrove ecosystems which includes the ecological structure of R. apiculata in Riau Province. Collecting data of mangrove vegetation condition was done by transect line and plot. The line transect was drawn from the reference point (the outer mangrove stand) with the direction perpendicular to the coastline to the mainland and made plots according to the category. The results showed that the population of R. apiculata was found in large numbers at Station 3 (350 ind) and a small/small amount was found at Station 1 (137 ind). In addition, Stations 1, 2 and 4 have only one grouping population of R. apiculata based on the Bhattacharya method, while Station 3 has two groupings. Furthermore, the highest R. apiculata density for tree category was obtained at Station 4 (1433.33 ind/m2), saplings category at Station 3 (10488.89 ind/m2) and seedlings category at Station 4 (3666667 ind/m2). Furthermore the water temperature ranged from 28.3 – 30.7°C, salinity 27.3 – 31.3, pH 7.3 – 7.9, DO 5.2 – 6.4 and redox potential ranged from 102 – 124 mV. Based on the standard criteria and guidelines for determining mangrove damage according to the Decree of the Minister of Environment No. 201 of 2004, the population density of R. apiculata at the research location is still classified as medium and refers to the Decree of the State Minister of Environment No. 51 of 2004 concerning Sea Water Quality Standards for Marine Biota, as a whole the range of measured water quality parameters is still within tolerance limits for life mangroves.